2019
DOI: 10.3389/fimmu.2019.01330
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signaling and Insulin Resistance Facilitate Trained Immunity in Macrophages Through Metabolic and Epigenetic Changes

Abstract: Adaptation of the innate immune system has been recently acknowledged, explaining sustained changes of innate immune responses. Such adaptation is termed trained immunity. Trained immunity is initiated by extracellular signals that trigger a cascade of events affecting cell metabolism and mediating chromatin changes on genes that control innate immune responses. Factors demonstrated to facilitate trained immunity are pathogenic signals (fungi, bacteria, viruses) as well non-pathogenic signals such as insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 87 publications
4
61
0
1
Order By: Relevance
“…Differential accessibility analysis, based on MACS2-defined peak regions for GMPs and neutrophils from β-glucan-treated mice compared with the respective cells from control-treated mice, revealed differentially accessible regions (DARs) in GMPs and neutrophils upon induction of trained immunity ( Figure 5 E). The top 10 significantly enriched GO terms in GMPs and neutrophils, identified on the basis of genes annotated to regions more accessible due to β-glucan-induced training, not only revealed terms such as “regulation of myeloid cell differentiation,” but also cell metabolism-related terms ( Figure 5 E), consistent with the findings of the RNA sequencing results from TANs ( Figure 2 C) and with the previously described involvement of immunometabolic pathways in the induction of trained immunity ( Arts et al., 2016 ; Ieronymaki et al., 2019 ).
Figure 5 Epigenetic Rewiring of Trained Granulopoiesis Splenic neutrophils and BM GMPs were sorted from mice that were treated with β-glucan or with PBS 7 days earlier and scATACseq was performed.
…”
Section: Resultsmentioning
confidence: 99%
“…Differential accessibility analysis, based on MACS2-defined peak regions for GMPs and neutrophils from β-glucan-treated mice compared with the respective cells from control-treated mice, revealed differentially accessible regions (DARs) in GMPs and neutrophils upon induction of trained immunity ( Figure 5 E). The top 10 significantly enriched GO terms in GMPs and neutrophils, identified on the basis of genes annotated to regions more accessible due to β-glucan-induced training, not only revealed terms such as “regulation of myeloid cell differentiation,” but also cell metabolism-related terms ( Figure 5 E), consistent with the findings of the RNA sequencing results from TANs ( Figure 2 C) and with the previously described involvement of immunometabolic pathways in the induction of trained immunity ( Arts et al., 2016 ; Ieronymaki et al., 2019 ).
Figure 5 Epigenetic Rewiring of Trained Granulopoiesis Splenic neutrophils and BM GMPs were sorted from mice that were treated with β-glucan or with PBS 7 days earlier and scATACseq was performed.
…”
Section: Resultsmentioning
confidence: 99%
“…These effects of insulin are mediated by its signal transduction pathway involving the insulin receptor and insulin like growth factor 1 receptor on the cell membrane [46]. Binding of insulin on the insulin receptor or insulin like growth factor 1 receptor (IGF1R) results in the phosphorylation of insulin receptor substrate 1/2 (IRS1/2) at its tyrosine residues, which results in the subsequent activation of two main pathways, the phosphoinositide3-kinase(PI3K)/protein kinase B (AKT) pathway and the mitogen-activated protein kinase (MAPK) pathway [46,47].…”
Section: Insulin Signaling and Insulin Resistancementioning
confidence: 99%
“…Organisms lacking adaptive immunity were shown to have enhanced resistance to subsequent infections (trained immunity). Innate trained immunity occurs in human monocytes and MØ; mTOR/Akt/PI3K‐regulated metabolic reprogramming, including increased glutamine metabolism, a shift from OXPHOS‐to‐aerobic glycolysis, and cholesterol synthesis contribute to this process 10‐104 . However, IAV also alters these pathways, and one study found trained immunity had no effect on IAV infection 15 …”
Section: The Immune Response To Influenza Infectionmentioning
confidence: 99%